Investigation of the Wavy Channel Cold Plate Thermal Performance - Chin, Yu Hong (2019)
Liquid cold plate helps dissipate excess heat from electronic devices during operation, thus prevents overheating of the devices. This project was conducted by first carrying out literature reviews on the relevant topic. Based on the reviews, it was found that the larger the contact area between the coolant and the heat source, the more heat will be removed. Also, recirculation flow of coolant will improve the heat removal performance as well. Thus, from the Part 1 of the project, the design concept of wavy channels cold plate with secondary branches have been selected. The contours were attached from A-1 to A-4. In the Part 2 of the project, Computer-Aided Design modelling (SOLIDWORKS) and fluid flow simulation (ANSYS CFX) were then being carried out back and forth to obtain the cold plate design with the optimised thermal performance. In order to have a more structured modelling and simulation process, the Taguchi Method was applied to narrow down the number of possible designs. The spreadsheet created for the Method was attached in the Appendices section from A-5 to A-8. As for this project, the desired temperature difference of heat source across the cold plate design was set to be close to 5 ℃ under a fluid mass flow rate of 50 g/s. If the desired temperature difference value was met, that particular cold plate design would be chosen to undergo further flow simulations to determine the thermal performance of that design under different fluid mass flow rates of up to 100 g/s. Besides temperature difference, the pressure variation of fluid across the cold plate were studied to ensure that the drops would not damage the structure of the cold plate made of 6061 aluminium alloy. In fact, the pressure drops should be lower than the tensile yield strength of 276 MPa and Ultimate Yield Strength of 310 MPa for a 6061 Aluminium plate (ASM Aerospace Specification Metals Inc., 2018). In this project, an aluminium wavy channel cold plate (200 mm × 130 mm × 17 mm), with channels depth of 14 mm, added with 74 secondary channels, was designed to enhance the occurrence of flow recirculation and heat dissipation. The equal width of the wavy channels and the design of the inlet as well as outlet dividers help stabilise the drops in fluid pressure across the cold plate. Lastly, milling toolpaths of the finalised design was generated through MasterCAM before being transmitted to CNC milling machine for fabrication. After 31 days of machining, using 1.5 mm, 2 mm and 4 mm end mills, the prototype was produced and ready to be sent for documentation.